2021
DOI: 10.1016/j.supflu.2021.105249
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination and modelling of high-pressure phase behavior for the binary system CO2 + cyclooctane

Abstract: Experimental determination and modelling of high-pressure phase behavior for the binary system CO 2 + cyclooctane 2 Highlights  High-pressure phase equilibria were measured for the system CO 2 + cyclooctane  80 bubble points and 16 dew points were acquired  The experimental data were obtained using a variable volume high-pressure cell  The studied binary system probably exhibits a type V phase behavior  Data were correlated with the Peng-Robinson equation and advanced mixing rules

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…10,11 From the results reported in this paper, it can be concluded that the binary system CO2 + cycloheptane also belongs to type I or II since the vapor-liquid critical curve is, highly likely, continuous. Finally, the binary mixture CO2 + cyclooctane probably exhibits type V phase behavior 3 but more experiments are necessary to validate this assumption.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10,11 From the results reported in this paper, it can be concluded that the binary system CO2 + cycloheptane also belongs to type I or II since the vapor-liquid critical curve is, highly likely, continuous. Finally, the binary mixture CO2 + cyclooctane probably exhibits type V phase behavior 3 but more experiments are necessary to validate this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Even in the oil and gas sector, high-pressure phase equilibrium data as well as thermodynamic data regarding to uncommon molecules (such as naphthenic components with more than six carbon atoms in ring or with multiple aromatic ring) are welcomed. 1,3 Due to the important role of carbon dioxide in the chemical, pharmaceutical and petrochemical industries, phase equilibrium data of mixtures containing CO2 remain crucial. [4][5][6][7][8] In our previous works 3,9 , a lack of data for two kinds of binary systems containing carbon dioxide + a naphthenic compound was noticed; they are CO2 + branched naphthenes and CO2 + naphthenes that contains more than 6 carbon atoms in ring (cycloheptane, cyclooctane, etc.).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations